The Effect of Innovation on Competitiveness in the Food Processing Industry of Cameroon: A Mediating Effect of Quality Management - Nicholas, Baninla; Sama, Molem C.; Emmanuel, Nwahanye (European Scientific Journal, ESJ, 2024)
With the intensification of national and global competition, the focus of companies is now on how to achieve competitive advantage. With globalisation, Cameroon’s industry is facing specific difficulties such as unchecked competition from imports, internal weaknesses in output, low technology acquisition as well as poor links between industry and the institutional sector, making competition a problem for them. This led to the foundation of studies on innovation and competitiveness, but at this point, there are still inconclusive results. This paper focuses on examining the effect of innovation on competitiveness in the food processing industry of Cameroon, with a specific emphasis on the mediating effect of quality management. This study adopted the cross-sectional research design for its investigation. The primary source of data was used for this study, as it was current. This primary data was collected through the distribution of questionnaires to the respondents. Innovation in this study was captured in terms product, process, market, and organisational innovations. Quality management on the other hand was captured in terms of commitment to quality, employee involvement, customer focus, process monitoring, incentives, and recognition. In relation to competitiveness, the study focused on productivity, output growth, and market share. Data was collected from 335 managers of food processing companies drawn randomly after stratification from a population of 2564 food processing companies operating in Cameroon. This includes Douala, Yaounde, Ngaoundere, Buea, Bafoussam, Maroua, and Bertoua with 201, 40, 34, 3, 30, 17, and 10 as corresponding sample proportions respectively. Inferential statistics was used during the analysis of the data, specifically using Baron and Kenny’s approach of testing the mediation hypothesis. Based on the results, there were traces of positive and significant direct effects of product, process, and organisational innovations on competitiveness. On the other hand, market innovation was insignificant. In terms of the indirect effect, the study revealed a partial mediation of quality management in the effect of product innovation on competitiveness. Quality management, however, had no mediating role on other dimensions of innovation (process, market, and organisational) and competitiveness.